Mechanical properties of low temperature irradiated magnesium - Pomar, Cayetano; Blewitt, T. H.; Bisogni, E. A. (John Wiley & Sons, 1972)
Fil: Pomar, Cayetano Comisión Nacional de Energía Atómica; Argentina